One Size Fits all or Tailor‐Made? Building Appropriate Certification Systems for Geographical Indications in Southeast Asia. Issue 2 (1st March 2017) - Marie‐Vivien, Delphine; Vagneron, Isabelle
Abstract : Geographical indications (GIs)—i.e. indications identifying goods originating in a specific place and having quality, characteristics, and reputation attributable to their geographical origin—are developing fast in the Southeast Asian food sector, with a wide range of new products such as Khao Hom Mali and Thung Kula Rong‐Hai (fragrant rice), Kampot pepper, or Nuoc Mam Phu Quoc (fish sauce). After concentrating their efforts on registering GIs (to protect the name against counterfeit), GI promoters needed to decide how to control product compliance with GI specifications for specific quality. This paper analyzes the control and certification procedures for GIs in four Southeast Asian countries—Thailand, Vietnam, Cambodia, and Laos—and the challenges faced in building an efficient yet appropriate system of controls in these countries. Influenced by the "gold standard" of certification in place of organic agriculture, finding appropriate GI control systems is one of the dilemmas faced by these countries. The article discusses the main differences between GIs and other agricultural standards—specifications that are unique to each GI, endogenous, and based on local production practices—and the consequences in terms of certification. Indeed, in the case of GIs, other options than private third‐party certification could better ensure that GI rules are followed, which may rely on the knowledge producers and connoisseurs have of the product.